Data Service Providers' Participation in Data Black Market Governance Based on Evolutionary Games - Fengling ZHANG, Xiaoqi MA (Nongye tushu qingbao xuebao)
[Purpose/Significance] In the context of China's commitment to the development of the data element circulation market, the governance of the data black market has emerged as a pressing issue that demands urgent attention. The purpose of this paper is to discuss the implementation of the operating law of the market economy, the utilization of the interaction of multiple parties with interests in the data circulation market to achieve meaningful participation in the governance of data service providers, the curbing of the black market trading of data elements, and the achievement of the goal of reducing the government's management costs and helping the data trading market to break through the black market shroud. [Methods/Processes] A four-party evolutionary game model is used to simulate the dynamic interaction strategy choices and the results of evolutionary stabilization strategies of data service providers, data enterprises, data black market participants and regulators in data factor circulation configuration. The study explores the conditions necessary for transforming data service providers into active participants to validate the effectiveness of the data service providers' participation in the governance mechanism. The study also discusses the methods by which the goal of enhancing the effectiveness of the data service providers' participation in the governance mechanism may be achieved. This is accomplished through the design of multi-party interaction mechanisms, and the input-output ratio of the participation governance mechanism in curbing black market trading. [Results/Conclusions] The simulation results demonstrate that by designing mechanisms in four aspects: policy, reputation, cooperation, and punishment, the participation governance mechanism of data service providers can reduce the regulatory pressure on data black markets, enhance policy flexibility, and minimize governance costs. In particular, the effect is most significant when both data service providers and data enterprises pursue long-term cooperation and reputational benefits. Specifically, 1) policy support can stimulate the potential and motivation of data service providers in governing black markets. 2) Under the reputation and cooperation mechanism, the participation of data service providers in the governance mechanism can not only help the regulator and enterprises to reduce the regulatory pressure, but also enhance the willingness of data enterprises to take the initiative in combating black market transactions and form the synergy of multi-party collaborative governance. 3) Adequate government regulation and a suitable system of sanctions can ensure the effective participation of data service providers in the governance of the black market, and ensure that the participation of data service providers in the governance and government regulation forms a synergy. Accordingly, the design and maintenance of the mechanism for data service providers' participation in governance is proposed, covering four aspects: an incentive mechanism, multiple forms of cooperation, a penalty mechanism, and technical guarantee.